C5a/C5aR1 mediates IMQ‐induced psoriasiform skin inflammation by promoting IL‐17A production from γδ‐T cells - Zheng, Quan‐you; Xu, Feng; Yang, Yi; Sun, Dao‐dong; Zhong, Yu; Wu, Shun; Li, Gui‐qing; Gao, Wei‐wu; Wang, Tao; Xu, Gui‐lian; Liang, Shen‐ju (The FASEB journal, 2020)
Psoriasis is a chronic relapsing inflammatory skin disease, affecting up to 3% of the global population. Accumulating evidence suggests that the complement system is involved in its pathogenesis. Our previous study revealed that the C5a/C5aR1 pathway is crucial for disease development. However, the underlying mechanisms remain largely unknown. To explore potential mechanisms, psoriatic skin lesions and histological changes were assessed following imiquimod (IMQ) cream treatment. Inflammatory cytokine expression was tested by real‐time RT‐PCR. Immunohistochemistry and flow cytometry were used to identify inflammatory cell infiltration and interleukin (IL‐17A) IL‐17A expression. A C5aR1 antagonist (C5aR1a) and PI3K inhibitor (wortmannin) were used for blocking experiments (both in vivo and in vitro) to explore the mechanism. C5a/C5aR1‐pathway inhibition significantly attenuated psoriasis‐like skin lesions with decreased epidermal hyperplasia, downregulated type 17‐related inflammatory gene expression, and reduced IL‐17A‐producing γδ‐T cell responses. Mechanistically, C5a/C5aR1 promoted the latter phenotype via PI3K‐Akt signaling. Consistently, C5aR1 deficiency clearly ameliorated IMQ‐induced chronic psoriasiform dermatitis, with a significant decrease in IL‐17A expression. Finally, blocking C5aR1 signaling further decreased psoriasiform skin inflammation in IL‐17‐deficient mice. Results suggest that C5a/C5aR1 mediates experimental psoriasis and skin inflammation by upregulating IL‐17A expression from γδ‐T cells. Blocking C5a/C5aR1/IL‐17A axis is expected to be a promising strategy for psoriasis treatment.